Solving the Equation: (5x  5 + 5x²)  (3x² + 2x) = 2x² + 6x  6
This article will guide you through the steps to solve the given equation.
1. Simplify both sides of the equation:

Left side:
 Distribute the negative sign: 5x  5 + 5x²  3x²  2x
 Combine like terms: 2x² + 3x  5

Right side: Remains the same: 2x² + 6x  6
2. Rearrange the equation to set it equal to zero:
Subtract the terms on the right side from both sides: (2x² + 3x  5)  (2x² + 6x  6) = 0
Simplify by combining like terms: 3x + 1 = 0
3. Solve for x:
 Subtract 1 from both sides: 3x = 1
 Divide both sides by 3: x = 1/3
Solution:
Therefore, the solution to the equation (5x  5 + 5x²)  (3x² + 2x) = 2x² + 6x  6 is x = 1/3.